INARI DECLARATION 2002 on the occasion of the Third Ministerial Meeting of THE ARCTIC COUNCIL - Arctic Council, - (Arctic Council, 2002)
INARI DECLARATION on the occasion of the Third Ministerial Meeting of THE ARCTIC COUNCIL, October 2002